THE INFLUENCE OF TRENDS, LIFESTYLE, CONSUMERISM ON COFFEE PURCHASING DECISIONS IN MEDAN CITY (ISLAMIC ECONOMIC PERSPECTIVE) - Harahap, Miftah Rizki Addin; Siregar, Muhammad Habibi; Syahriza, Rahmi (Pena Cendekia Insani, 2025)
This study aims to analyze the influence of trends, lifestyles, and community consumerism on coffee production in Medan City and examine the urgency of halal certification in this context. Using a quantitative approach with phenomenological properties, this study involves collecting data through questionnaires distributed to consumers and coffee business actors in Medan City. The analysis was carried out to determine the relationship between variables using descriptive and inferential statistical methods. The results of this study show that trends, lifestyle, and consumerism significantly affect coffee purchase decisions in Medan City. Trends contributed 13.47%, lifestyle 9.49%, and consumerism 7.89%, with a total simultaneous contribution of 18.1%. Coffee consumption now reflects social identity, self-existence, and visual cultural pressures, not just functional needs. In the review of sharia economics, this pattern shows a tendency of excessive consumption (israf) and symbolism that is contrary to the principles of halal-thayyib, tawazun (balance), and wasathiyah (moderation). Therefore, consumption needs to be directed towards spiritual awareness, blessings, and ethical values.